Effect of a composite mixture of emblica officinalis, Terminalia chebula and terminalia bellirica on aflatoxicosis in rabbits - Indu K (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2009)
Among the various mycotoxins, aflatoxins have been the subject of most intensive research because of the extremely potent cytotoxic and carcinogenic effects. Mycotoxicosis and its counteraction have received greater attention by researchers in the last few decades. In this context an evaluation study on the protective effect of a herbal composite mixture triphala (containing Emblica officinalis, Terminalia chebula and Terminalia bellirica) on aflatoxicosis in rabbits was carried out.